Characterization of Site-Specific Phosphorylation of NF-κB p65 in Retinal Cells in Response to High Glucose and Cytokine Polarization - Haoshen Shi; Elizabeth A. Berger (Mediators of Inflammation)
Background. Inflammation is an important contributor to the pathogenesis of diabetic retinopathy (DR). NF-κB is a master transcriptional regulator for numerous inflammatory genes. Although NF-κB is comprised of multiple subunits, p65 has received the most attention. However, the p65 subunit can be phosphorylated at numerous sites, for which the effects of DR-related conditions are not well characterized. Since dysregulation of NF-κB has been linked to chronic inflammation, the current study examines site-specific p65 phosphorylation in retinal cells exposed to high glucose and investigates the effects of cytokine polarization. Methods. Phosphorylation of NF-κB p65 sites was examined in human primary retinal endothelial cells (HREC) and MIO-M1 Müller cells after exposure to high glucose (HG) and pro- or anti-inflammatory cytokines. Related downstream gene activation was selectively measured by real-time RT-PCR, ELISA, and/or Western blot. Results. HG exposure resulted in differential phosphorylation of p65 subunit sites between HREC and Müller cells. Proinflammatory cytokines further increased phosphorylation of these sites and additional sites that were not altered in HG. In contrast, IL-4 exhibited a suppressive effect on the phosphorylation of p65 sites in both cell types and promoted IκBα expression. Downstream inflammatory mediators were increased in response to proinflammatory cytokine treatment versus HG exposure. IL-4 inhibited proinflammatory cytokines, while IL-10 was enhanced despite HG exposure. Conclusion. The current study is the first to characterize HG-induced NF-κB p65 phosphorylation after cytokine polarization. By understanding NF-κB phosphorylation and cytokine influence during hyperglycemic conditions, intervention points can be identified for early-stage treatment of DR.